Hepatitis B surface antigen positivity is associated with poor short- and long-term outcomes in patients with diffuse large B-cell lymphoma who received CHOP or R-CHOP - Zhan, Zhumei; Guo, Wei; Wan, Xin; Wang, Bowen; Li, Jia; Wang, Haotian; Li, Zhe; Huang, Yuhua; Young, Ken H.; Bai, Ou (Frontiers in Immunology, 2024)
The development of diffuse large B-cell lymphoma (DLBCL) is closely related to the host infection status. China is a highly endemic area for hepatitis B virus (HBV) infection. It is not clear whether HBV infection has a consistent effect on the prognostic implications of patients with DLBCL in different treatment settings. We conducted a cohort study of 692 patients with DLBCL receiving three or more cycles of treatment with a CHOP or R-CHOP regimen from the First Hospital of Jilin University between July 2011 and July 2022. The patients were divided into two groups based on their hepatitis B surface antigen (HBsAg) status: HBsAg-positive (n = 84, 12.1%) and HBsAg-negative (n = 608, 87.9%) groups. Tumor specimens from 180 patients with primary DLBCL were collected for next-generation sequencing (NGS). The HBsAg-positive group had more frequent abnormal liver function (P = 0.003), hypoalbuminemia (P < 0.001), incidence of ＞2 extranodal organs (P = 0.011), and spleen involvement (P < 0.001) than the HBsAg-negative group.HBsAg-positive patients had lower complete response (CR) and overall response rates (ORR) rates (all the p values ＜0.05), in either the CHOP group or R-CHOP group. Among patients receiving R-CHOP, the rates of disease progression within 12 and 24 months were higher in the HBsAg-positive group than in the HBsAg-negative group (P=0.018, P=0.029). However, no significant difference in disease progression was observed between HBsAg-positive and HBsAg-negative patients in the CHOP group(P＞0.05). HBsAg positivity (OS: HR [95% CI] = 2.511 [1.214-5.192], P = 0.013) was only associated with poorer OS in the CHOP group. Whereas in the R-CHOP group, HBsAg positivity was associated with both poorer OS and PFS (OS: HR [95% CI] = 1.672 [1.050-2.665], P = 0.030; PFS: HR [95% CI] = 1.536 [1.013-2.331], P = 0.043). Additionally, HBsAg-positive patients with DLBCL also had a higher prevalence of mutations in MYC, ATM, PTPN6, and epigenetically regulated genes.These findings suggest that HBsAg-positive DLBCL patients may represent a distinct subgroup with a poorer prognosis. The standard therapies may be insufficient and new therapeutic strategies should be developed based on a better understanding of the underlying mechanisms of chemoresistance.